Can we predict the landing performance of simulated aerials in surfing?. Issue 22 (17th November 2021) - Forsyth, James R.; Tsai, Ming-Chang; Sheppard, Jeremy M.; Whitting, John W.; Riddiford-Harland, Diane L.; Steele, Julie R.
ABSTRACT: This study explored which technical and physical attributes could predict superior and/or safe landing performance when surfers performed variations of a simulated aerial task. Fourteen surfers (age 20.6 ± 5.7 years, height 178.1 ± 9.50 cm, mass 70.6 ± 10.8 kg) had their lower limb mobility, squat jump, countermovement jump, and drop-and-stick landing performance assessed. Performance of two aerial variations (Frontside Air (FA) and Frontside Air Reverse (FAR)) was also measured, with variables relating to technical performance (critical feature and subjective ratings) and potential injury risk (relative total peak landing force and loading rates) collected. Multiple linear regressions were used to predict performance of both aerial variations based on a subset of independent variables. Four models could predict performance. Predicted technical capability in the FAR was mostly influenced by lead limb hip extension and lead limb knee flexion range of motion. Potential injury risk when surfers perform an FA and FAR was predicted to be mitigated by increasing lead ankle dorsiflexion range of motion, as well as trail hip extensor mobility to reduce the relative total peak force experienced when landing the FA. These simple outcome measures could be routinely assessed to ensure successful and safe aerial landings in surfing.